Effect of Mediterranean Diet Enriched in High Quality Extra Virgin Olive Oil on Oxidative Stress, Inflammation and Gut Microbiota in Obese and Normal Weight Adult Subjects - Luisi, Maria Luisa Eliana; Lucarini, Laura; Biffi, Barbara; Rafanelli, Elena; Pietramellara, Giacomo; Durante, Mariaconcetta; Vidali, Sofia; Provensi, Gustavo; Madiai, Sara; Gheri, Chiara Francesca; Masini, Emanuela; Ceccherini, Maria Teresa (Frontiers in Pharmacology, 2019)
The Mediterranean Diet (MD) is useful in the prevention of overweight, obesity and metabolic disease. High Quality Extra Virgin Olive Oil (HQ-EVOO), an essential component of this diet, exerts protective effects against chronic diseases. Gut Microbiota (GM), recognized as a key factor in driving metabolic activities, is involved in the regulation of host immunity. Lactic Acid Bacteria (LAB) and their probio–active cellular substances produce beneficial effects in the gastrointestinal tract. 18 overweight/obese subjects (cases, BMI ≥ 25 Kg/m2) and 18 normal weight controls (BMI 18.5-24.9Kg/m2) were fed with MD enriched with 40g/die HQ-EVOO for three months. Feces and blood samples were collected at time 0 (T0) and after three months (T1) for LAB composition, oxidative stress, metabolic and inflammation parameter determinations. Myeloperoxidase and 8‐hydroxy‐2‐deoxyguanosine, markers of inflammation and oxidative stress, were significantly decreased after MD rich in HQ-EVOO both in controls andthan in cases. Proinflammatory cytokines levels were significantly decreased in cases in comparison to controls, while IL-10 and adiponectin were significantly increased in cases. LAB’s rpoB copies/ng of DNA increased 55.6 fold in cases compared to their baseline after MD rich in HQ-EVOO. MD rich in HQ-EVOO increaseds adiponectin and IL-10 concentration in overweight/obese subjects and decreaseds oxidative stress and inflammation parameters and at the same time, increaseds LAB number in GM. Our results indicate that MD rich in HQ-EVOO let induces an increase of LAB in GM and could have a potential role in the prevention of inflammation and oxidative stress in normal weight and overweight/obese subjects.